2012
DOI: 10.1891/2156-5287.2.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Classification Tool to Determine Groups of Women That Contribute to the Cesarean Section Rate: Establishing a Baseline for Clinical Decision Making and Quality Improvement

Abstract: OBJECTIVE:To identify the groups of women who are the largest contributors to the cesarean section rate at a maternity facility in South East Queensland, Australia. Examining the characteristics of these women will allow the development of unit-focused initiatives aimed at reducing cesarean sections in these groups of women. METHOD:A modified version of the Robson Ten Group Classification System was identified as the most appropriate tool to determine cesarean section rates in different groups of women. A pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Given that the largest risk factor for having a caesarean section is having had a previous caesarean section, 42 attention should be given to reducing caesarean section rates in nulliparous women and those with previous caesarean section births. A number of interventions -caseload midwifery, 43 chart audit 44 and induction of labour 45 -have been shown to reduce the risk of caesarean section amongst low-risk nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the largest risk factor for having a caesarean section is having had a previous caesarean section, 42 attention should be given to reducing caesarean section rates in nulliparous women and those with previous caesarean section births. A number of interventions -caseload midwifery, 43 chart audit 44 and induction of labour 45 -have been shown to reduce the risk of caesarean section amongst low-risk nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors of two systematic reviews (Caughey et al, 2009;Gülmezoglu, Crowther, & Middleton, 2006) concluded that IOL does not increase the CS rate, a significant methodological critique of this work calls into question the appropriateness of routine IOL for well women and fetuses before 42 weeks' gestation (King, Pilliod, & Little, 2010;Mozurkewich, Chilimigras, Koepke, Keeton, & King, 2009). There is also increasing evidence that primiparous women having an IOL are the largest group contributing to the CS rate (Brennan, Murphy, Robson, & O'Herlihy, 2011;Slavin & Fenwick, 2012). Certainly, one could argue that the risk of stillbirth in extremely obese pregnant women perhaps justifies IOL.…”
Section: Discussionmentioning
confidence: 99%